Evaluation of muscle involvement & degeneration in advanced oral submucous fibrosis using three different stains – a retrospective cross-sectional study - Umashankar, Krishnapriya; J Sherlin, Herald; Jayaraj, Gifrina; Ravi Don, Kanchi; Santhanam, Archana (Brazilian Dental Science, 2021)
ABSTRACTBackground: Oral submucous fibrosis (OSMF) is graded according to various histological factors which include the epithelial changes and the connective tissue changes. These features could be identified in routine Hematoxylin and Eosin (H and E) staining in shades of pink. However, the use of special stains provides a contrast to various connective tissue components thereby aiding in better visualization of these connective tissue changes in advanced OSMF cases. Objective: To compare and evaluate muscle involvement and degeneration in advanced oral submucous fibrosis using three different stains namely, H&E, Van Gieson, and Masson’s Trichrome. Material and Methods: 10 Formalin-fixed paraffin-embedded tissue sections of advanced OSMFwere stained using 3 different stains namely Hematoxylin and Eosin (H&E), Van-Gieson, and Masson trichrome. The results obtained were tabulated and statistically analyzed using Kruskal Wallis ANOVA. Results: The hyalinization and fibrosis involving the skeletal muscle were better visualized in Masson’s Trichrome but were not statistically significant. The muscle degeneration in deeper areas was better visualized in Masson’s trichrome when compared to the H&E and Van Gieson. Conclusion: Hematoxylin and eosin stains all the connective tissue components in various shades of pink, use of special stains bestows contrast between different components of connective tissue, thus improvising grading of OSMF. Masson’s trichrome stain can be used as a single adjunct to hematoxylin and eosin stain as changes in the superficial and deeper connective tissue could be ascertained.KeywordsFibrosis; Masson’s trichrome stain; Muscle degeneration; Oral submucous fibrosis grading.